2012
DOI: 10.1515/cclm-2012-0657
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of cancer biomarkers in diabetic and non-diabetic proteinuric patients: a preliminary study

Abstract: CBs levels seem to be changed in different proteinuric patients. This condition should be kept in mind when evaluating CBs levels in proteinuric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
1
13
5
Order By: Relevance
“…Gul et al found significant correlation between CA19-9 and HbA1c in diabetic patients [10]. There is only one study investigating CEA levels in diabetes mellitus, which found lower CEA levels in diabetics than controls, which contradicts our results [12]. The researchers also found higher CA19-9 levels, and they did not correlate these markers with HbA1c.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Gul et al found significant correlation between CA19-9 and HbA1c in diabetic patients [10]. There is only one study investigating CEA levels in diabetes mellitus, which found lower CEA levels in diabetics than controls, which contradicts our results [12]. The researchers also found higher CA19-9 levels, and they did not correlate these markers with HbA1c.…”
Section: Discussioncontrasting
confidence: 93%
“…There is a relation between endocrine and exocrine pancreas reserve [11]. To our knowledge, there is only one study investigating CEA levels in diabetes mellitus, which found lower CEA levels in diabetics than controls [12]. In the above-mentioned studies, tumor markers were not studied after euglycemia was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the mechanism through which DM and prostate cancer are related has not been fully elucidated. Men with DM are known to generally have lower prostate-specific antigen (PSA) level but larger prostate size than others not having DM (Hammarsten and Hogstedt, 2001;Berger et al, 2005;Werny et al, 2006;Fowke et al, 2007;Turgutalp et al, 2013). Also, it can be suggested that the reported protective effect of DM may be due to the differences in PCa screening among diabetic and non-diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Serum and plasma have become the most widely used sample for diabetic biomarker studies212223. Depletion of serum prior to proteomic analysis by immunoaffinity subtraction of specific proteins through the use of targeted polyclonal antibody columns and spin filters has recently emerged as a promising tool for serum prefractionation19.…”
mentioning
confidence: 99%